Methylxanthine and Flavonoid Contents from Guarana Seeds (Paullinia cupana): Comparison of Different Drying Techniques and Effects of UV Radiation - André Luiz Sampaio da Silva Junior; Madson Moreira Nascimento; Herick Macedo Santos; Ivon Pinheiro Lôbo; Rosilene Aparecida de Oliveira; Raildo Mota de Jesus (International Journal of Food Science)
Guarana seeds are typically processed using one of three drying methods: traditional sun exposure, greenhouse drying, or the alguidar oven technique. In our research, we evaluated the contents of methylxanthines and flavan-3-ols in sun- and alguidar-dried guarana seeds from Bahia State’s Low Sul Identity Territory. Caffeine, theobromine, catechin, and epicatechin were determined by high-performance liquid chromatography with UV-visible detection (HPLC/UV-vis). Statistical tools, including analysis of variance (ANOVA), Tukey’s test, and exploratory analysis, were employed to analyze the obtained data. Our findings indicated that the flavan-3-ols content in sun-dried guarana samples was lower compared to those dried using the alguidar oven, possibly due to exposure to ultraviolet radiation from solar energy. Conversely, we observed no significant differences (p>0.05) in the average contents of methylxanthines between the two drying methods. Our supplementary experiments involving UV-A and UV-C radiation lamps revealed a decreasing trend in methylxanthines and flavan-3-ols contents with increasing duration of UV radiation exposure.